THE EFFECT OF PRODUCT INNOVATION, AND PRICES ON REPURCHASE INTEREST IN CONSUMER SATISFACTION MEDITED ON MSME WINGKO BABAT - Hidayat, Moh. Nur; Muhtarom, Abid; Sutinem, Sutinem; Sugiarto, Edie; Kusbandono, Danu (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
Competition in the business world began to give birth to various ways to be able to attract the attention of customers and keep these customers in order to buy the products previously offered. Intense competition in a business. Business actors are aggressively marketing superior products. These superior products have differences in terms of innovation and price. Researchers used quantitative methods with a sample of 160 respondents. The data analysis used is the SEM method with the Smart PLS version 3.0 tool. The test used consists of the outer model, inner model, mediation test and hypothesis testing. Product innovation variables, Price, Purchase Interest, Consumer Satisfaction are valid and reliable.